PENGARUH GROWTH OPPORTUNITY, FIRM SIZE, LEVERAGE DAN NET WORKING CAPITAL TERHADAP CASH HOLDING - Nathania, Theofanne Adriel; Tjakrawala, F.X. Kurniawan (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
Obtain evidence relating to the effect of growth opportunity, firm size, leverage and net working capital on cash holding with the research subject of companies with the manufacturing sector listed on the Indonesian Stock Exchange in 2016-2020 or 5 consecutive years with a sample size of 59 companies in the manufacturing sector after determining the minimum number of samples using the Slovin formula and sorting using the purposive sampling method is the purpose of why this research was carried out. The use of the SPSS 25 program is applied in processing research data so that research results such as growth opportunity have a positive and significant impact on cash holding. Then, leverage along with net working capital has a significant negative effect on cash holding. Meanwhile, firm size has a positive but not significant effect on cash holding.